2010
DOI: 10.1111/j.1365-2729.2010.00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation provisioning with respect to learning styles in a Web‐based educational system: an experimental study

Abstract: Personalized instruction is seen as a desideratum of today's e-learning systems. The focus of this paper is on those platforms that use learning styles as personalization criterion called learning style-based adaptive educational systems. The paper presents an innovative approach based on an integrative set of learning preferences that alleviates some of the limitations of similar systems. The adaptive methods used as well as their implementation in a dedicated system (WELSA) are presented, together with a tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
11

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(75 citation statements)
references
References 25 publications
2
62
0
11
Order By: Relevance
“…We also plan to design, implement and validate new kind of proactive scenarios in order to enhance other functions of LMS, as well as adding new functions to LMS like computer-supported collaborative learning through the proactive and context-aware dynamic management of networks of interest among e-learners. The ultimate goal is the creation of a truly social, personal and adaptive online learning environment, as it is also envisioned in [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also plan to design, implement and validate new kind of proactive scenarios in order to enhance other functions of LMS, as well as adding new functions to LMS like computer-supported collaborative learning through the proactive and context-aware dynamic management of networks of interest among e-learners. The ultimate goal is the creation of a truly social, personal and adaptive online learning environment, as it is also envisioned in [4].…”
Section: Discussionmentioning
confidence: 99%
“…Please note that our approach of adaptive support can be merged with the approach proposed in [4] where an intelligent LMS is aimed at adapting the course to the learning preferences of each student. Indeed, to proactively provide context-aware and pertinent support messages to students while they study online is complementary to dynamically provide them with matched course contents according to their learning styles.…”
Section: Adaptive Supportmentioning
confidence: 99%
“…Çalışmanın sonuçlarına göre deney grubundaki öğrencilerin daha verimli öğrenim gördükleri sonucunu ortaya koymaktadır. WELSA (Popescu, 2009;Popescu, 2010) sisteminin değerlendirilmesine yönelik 64 öğrenci ile deneysel bir çalışma yürütülmüştür. Çalışmanın sonuçlarına göre uyarlanabilir yaklaşımda eşlenen ve eşlenmeyen gruplar arasında oldukça fark olduğu gibi uyarlanabilir yaklaşım ile uyarlanamayan yaklaşım arasında da oldukça farklılıklar gözlenmiştir.…”
Section: İlişkili çAlışmalarunclassified
“…Bu konuda bireylerin bilgiyi almada, kullanmada ve saklamada tercih ettikleri yol olarak kabul edilen öğrenme stilleri öne çıkmaktadır (Brown, 2007;Brown, vd., 2007;Latham, vd., 2010;Wolf, 2003). Yapılan birçok çalışmanın sonuçlarına göre belirli bir öğrenme stilinin kullanıldığı e-öğrenme ortamları öğrenciler için daha verimli, daha etkin, daha memnuniyet derecesi yüksek ve öğrenme zamanını azaltan öğrenme ortamlarıdır (Mustafa ve Sharif, 2011;Papanikolaou, vd., 2003;Popescu, 2009;Popescu, 2010;Sangineto, vd., 2008;Triantafillou, vd., 2003;Wang, 2008). Bu bakımdan öğrenme stilleri uyarlanabilir zeki e-öğrenme ortamlarının tasarımında kullanıcı modelinin oluşturulması için bir parametre olarak kabul edilebilir (Brown, 2007;Conlan, vd., 2002;Latham vd., 2010;Sangineto vd., 2008;Wang, 2008).…”
unclassified
“…In online education today, personalized instruction has become an essential element of an instructor's teaching practices and pedagogy (Popescu, 2010). Popescu's (2010) study found that presenting students with a learning environment that is antagonistic to a student's learning styles can decrease his or her effort, satisfaction and enthusiasm for learning (Popesu, 2010).…”
Section: Introductionmentioning
confidence: 99%